Identification of microRNA hsa-miR-30c-5p as an inhibitory factor in the progression of hepatocellular carcinoma and investigation of its regulatory network via comprehensive analysis. Issue 1 (1st January 2021) - Hu, Shangshang; Zhang, Jinyan; Fang, Xiaoyu; Guo, Guoqing; Dai, Jing; Sheng, Zhiyong; Li, Dongdong; Chen, Jiasheng; Zhang, Li; Liu, Chuanmiao; Gao, Yu
ABSTRACT: Hepatocellular carcinoma (HCC) is a primary liver cancer with high morbidity and mortality. An increasing number of abnormal gene expressions were identified to be associated with the progression of HCC. Previous studies showed that the hsa-miR-30 c-5p (miR-30 c), one of the miR-30 family members, might play a role in suppressing tumor progression in a variety of tumors. The present study aims to examine miR-30 c effects in the development of HCC. The role of miR-30 c in HCC was comprehensively investigated by using bioinformatics and experiments in vitro . The multiple databases were combined to predict and screen the target genes and upstream lncRNAs of miR-30 c, and then constructed a competitive endogenous RNA (ceRNA) regulatory network with miR-30 c as the central miRNA. The miR-30 c-related ceRNA regulatory network was also initially validated in vitro . The results showed that miR-30 c over-expression could inhibit proliferation, migration, invasion, induce apoptosis, and increase G0/G1 phase ratio of HCC cells. Three miR-30 c upstream lncRNAs and 12 miR-30 c target genes were expressed in HCC cells with increased expression and poor prognosis, and a miR-30 C-related ceRNA regulatory network was constructed. This study verified miR-30 c as an inhibitory factor in the progression of HCC and performed analyses on the miR-30 c regulatory network, which might provide potential target information for HCC prognoses and therapies. However, further experiments in vivo and studies including clinical trials will be conducted to validate our results.